2012
DOI: 10.1111/tid.12041
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance in rat islet isograft recipients after cytomegalovirus infection

Abstract: Impaired glucose tolerance in rat islet isograft recipients after cytomegalovirus infection Smelt, M.J.; de Haan, Bart; Faas, M.M.; de Haan, A.; de Vos, P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Historically, studies elucidating the link between viruses and hyperglycemia have focused on the role of viruses in inducing or exacerbating diabetes. These studies done both in vitro and in vivo in small animal models have utilized numerous viral pathogens, including herpes viruses ( 119 ), encephalomyocarditis virus (EMCV) ( 120 , 121 ), coxsackievirus B4 ( 122 ), and reoviruses ( 123 ). Infection by the viruses highlighted in these studies was shown to inflict cellular damage on beta cells, leading to hypoinsulinemia, and consequently causing hyperglycemia.…”
Section: Impact Of Hyperglycemia On Viral Immunitymentioning
confidence: 99%
“…Historically, studies elucidating the link between viruses and hyperglycemia have focused on the role of viruses in inducing or exacerbating diabetes. These studies done both in vitro and in vivo in small animal models have utilized numerous viral pathogens, including herpes viruses ( 119 ), encephalomyocarditis virus (EMCV) ( 120 , 121 ), coxsackievirus B4 ( 122 ), and reoviruses ( 123 ). Infection by the viruses highlighted in these studies was shown to inflict cellular damage on beta cells, leading to hypoinsulinemia, and consequently causing hyperglycemia.…”
Section: Impact Of Hyperglycemia On Viral Immunitymentioning
confidence: 99%